Effect of Grifola frondosa 95% ethanol extract on lipid metabolism and gut microbiota composition in high-fat diet-fed rats. Issue 12 (7th November 2018) - Pan, Yu-Yang; Zeng, Feng; Guo, Wei-Ling; Li, Tian-Tian; Jia, Rui-Bo; Huang, Zi-Rui; Lv, Xu-Cong; Zhang, Jiachao; Liu, Bin
Abstract : This study aimed to investigate the effects of 95% ethanol extract of G. frondosa (GF95) on lipid metabolism and gut microbiota composition in high-fat diet (HFD) fed rats. Abstract : This study aimed to investigate the effects of 95% ethanol extract of G. frondosa (GF95) on lipid metabolism and gut microbiota composition in high-fat diet (HFD) fed rats. UPLC/Q-TOF MS indicated that GF95 was enriched with flavones, fatty acids and so on. Meanwhile, we found that body weight, serum lipid or liver index (total cholesterol, triglyceride, and low density lipoprotein cholesterol) levels were significantly decreased in GF95-treated HFD-fed rats. Furthermore, GF95 treatment regulated mRNA expression levels involved in lipid metabolism. GF95 consumption significantly enhanced the excretion of bile acids in the cecum. Besides, in this study, a higher abundance of Butyricimonas genus was revealed in the GF95 group, which is highly related to the highest production of short-chain fatty acids in the caecum contents among the experimental groups. Interestingly, results from network analysis showed that Butyricimonas were negatively correlated with serum and liver lipid profiles.